2017
DOI: 10.1007/s00216-017-0718-7
|View full text |Cite
|
Sign up to set email alerts
|

Ionic liquid capillary columns for analysis of multi-component volatiles by gas chromatography-mass spectrometry: performance, selectivity, activity and retention indices

Abstract: This study investigates applications and performance evaluation of SLB-IL60, SLB-IL76 and SLB-IL111 columns, in relation to a DB-Wax column, for the analysis of coffee volatile compounds. Both standards and an authentic coffee sample were analysed, with solid-phase microextraction (SPME) sampling of the latter. A cryofocusing method was applied to improve resolution of the earliest eluting peaks using splitless injection SPME sample analysis. The Grob test was used to verify the inertness and efficiency of the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0

Year Published

2018
2018
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 29 publications
0
6
0
Order By: Relevance
“…The influence of sex and age on these potential markers seems to be of negligible importance, as only in some of the normalization methods slight tendencies for differences in sex or age were observed (see Table ). 2‐Methylfuran, guaiacol, 3‐methylbutanoic acid, and 2‐vinylfuran were detected in roasted coffee and are—such as 3,4‐dimethyl‐2,5‐furandion—a result of coffee roasting, therefore they can be viewed as plausible markers. Specificity is similarly questionable due to their formation during roasting processes.…”
Section: Discussionmentioning
confidence: 99%
“…The influence of sex and age on these potential markers seems to be of negligible importance, as only in some of the normalization methods slight tendencies for differences in sex or age were observed (see Table ). 2‐Methylfuran, guaiacol, 3‐methylbutanoic acid, and 2‐vinylfuran were detected in roasted coffee and are—such as 3,4‐dimethyl‐2,5‐furandion—a result of coffee roasting, therefore they can be viewed as plausible markers. Specificity is similarly questionable due to their formation during roasting processes.…”
Section: Discussionmentioning
confidence: 99%
“…The inertness of IL-based columns is a major concern for end-users. Studies have shown that IL-based stationary phases provide excellent resolution and efficiency, but their lack of inertness can make them less attractive . To overcome this limitation, different inert IL-based columns (SLB-IL60i, SLBIL76i, and SLB-IL111i) were introduced by MilliporeSigma in 2016.…”
Section: Chromatographic and Electrophoretic Separationsmentioning
confidence: 99%
“…Studies have shown that IL-based stationary phases provide excellent resolution and efficiency, but their lack of inertness can make them less attractive. 141 To overcome this limitation, different inert IL-based columns (SLB-IL60i, SLBIL76i, and SLB-IL111i) were introduced by Millipor-eSigma in 2016. Retention times and elution orders of analytes separated on these new inert columns were highly comparable with the previous generation of stationary phases.…”
Section: Et Al Employed the [C 6 Mim + ][Ntfmentioning
confidence: 99%
“…Applications of the commercial IL-based columns in the food field have been reported on by Garcia-Pinto et al, [8] and by Amaral et al, [9]. In the first study, microextraction by packed sorbents (MEPS) was coupled with gas chromatography with a set of IL SPs (SLB-IL59, SLB-IL61, SLB-IL76 and SLB-IL100) to determine haloanisoles (responsible for the so-called cork off-flavour) in wines.…”
Section: Exploiting the Peculiar Selectivity Of Ionic Liquids For The...mentioning
confidence: 99%